Congenital myopathy associated with the triadin knockout syndrome. (21st March 2017) - Engel, Andrew G.; Redhage, Keeley R.; Tester, David J.; Ackerman, Michael J.; Selcen, Duygu
Abstract : Objective: Triadin is a component of the calcium release complex of cardiac and skeletal muscle. Our objective was to analyze the skeletal muscle phenotype of the triadin knockout syndrome. Methods: We performed clinical evaluation, analyzed morphologic features by light and electron microscopy, and immunolocalized triadin in skeletal muscle. Results: A 6-year-old boy with lifelong muscle weakness had a triadin knockout syndrome caused by compound heterozygous null mutations in triadin. Light microscopy of a deltoid muscle specimen shows multiple small abnormal spaces in all muscle fibers. Triadin immunoreactivity is absent from type 1 fibers and barely detectable in type 2 fibers. Electron microscopy reveals focally distributed dilation and degeneration of the lateral cisterns of the sarcoplasmic reticulum and loss of the triadin anchors from the preserved lateral cisterns. Conclusions: Absence of triadin in humans can result in a congenital myopathy associated with profound pathologic alterations in components of the sarcoplasmic reticulum. Why only some triadin-deficient patients develop a skeletal muscle phenotype remains an unsolved question.